Kinetics of Betulin Oxidation over Gold Supported Heterogeneous Catalysts for Production of Pharmaceuticals; EuropaCat 2019. Catalysis without Borders; Poster Programme - Maki-Arvela P. Paivi; Hemming J. Jarl; Kari E. Eranen; Murzin D. Yu. Dmitry; Kolobova E. N. Ekaterina Nikolaevna; Buachidze A. R. Anna Romanovna; Pestryakov A. N. Aleksey Nikolaevich (2019, 2019)
Title screen